Restoration a novel - Bradley, John Ed (Doubleday, 2003)
More than sixty years after artist Levette Asmore committed suicide after destroying his most famous work, a controversial mural, journalist Jack Charbonnet and art restorer Rhys Goudeau discover that the painting may still exist.